The Influence The Influence Of Health Promotion Through E-Booklet Media On Knowledge About Gastritis Prevention In Adolescents At SMPN 5 Masbagik - Taufandas, Maruli; Aupia, Anatun; Ikhwani, Dina Alfiana; Muhsinin, Siti Zuraida; Khairari, Nandang DD. (JIKF, 2025)
Background : Gastritis, commonly known as stomach ache, is a prevalent disease in society, but it is often underestimated and disregarded by those affected. The variable in this study is health promotion throught e-booklets, and the dependent variable in this study is knowledge of gastritis prevention. Objective :To determine the effect of health promotion through e-booklet and leaflet media on knowledge of gastritis prevention among adolescents at SMPN 5 Masbagik. Method :This research employed a Quasi-Experimental study design involving two groups, aiming to describe the presence or absence of influence and comparison between e-booklet and leaflet media in enhancing adolescents' knowledge about gastritis prevention. The study involved 67 respondents with a stratified random sampling technique. Data were processed using statistical tests, Wilcoxon tests, and Mann-Whitney tests. Result :The study indicated that adolescents' knowledge about gastritis prevention before health promotion through e-booklet media was mostly in the poor category, with 23 respondents (68%), and after health promotion, most respondents were in the good category, with 26 respondents (76%). Meanwhile, knowledge about gastritis before health promotion through leaflet media was mostly in the poor category, with 22 respondents (67%), and after health promotion, an increase was found in the good category, with 23 respondents (70%). Thus, there was an effect before and after health promotion through e-booklet and leaflet media, with a p-value of 0.000 (<0.05).In this study, no significant differences were found between the two media with a value of p = 0.196 > α = 0.05. Conclusion :This study concluded that health promotion through e-booklet and leaflet media had an effect in enhancing adolescents' knowledge about gastritis prevention. However, no significant comparison was found between e-booklet and leaflet media, with a p-value of 0.196 > α = 0.05.